Chromoblastomycosis in a Diabetic Patient Without a History of Trauma. (September 2015) - Zarei, Mina; Schneider, Samantha; Villasante, Alexandra; Villada, Gabriel; Patel, Tejas; Hu, Shasa; Romanelli, Paolo
Abstract : Abstract: Chromoblastomycosis (CBM) is a slowly progressive cutaneous and subcutaneous mycosis mostly seen in tropical and subtropical areas and Fonsecaea pedrosoi is the most common cause. The authors describe the case of a diabetic Haitian woman, presenting with a chronic verrucous plaque without any history of trauma. Her histopathologic results showed epidermal hyperplasia and sclerotic bodies, which are diagnostic for CBM. Her therapy began with itraconazole 200 mg tablets twice a day. The unique feature of this patient is the coincidence of diabetes and CBM. However, to the best of our knowledge, this is the first documented case of human CBM in Miami, FL, which develops the awareness regarding this diagnosis among doctors in this area. There should be a close communication between dermatologists and pathologists to make an early diagnosis of CBM and also adequate therapy, which both are fundamental to improve patient's quality of life.